The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather